2019
DOI: 10.18203/2319-2003.ijbcp20194129
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of prescription writing practices in a government tertiary care hospital in Haryana by using WHO prescribing indicators

Abstract: Background: Writing a prescription is a combination of science and art. Good quality prescriptions are a sign of prescriber’s expertise. World Health Organization has defined certain parameters to promote rational drug use in all countries. This study was designed to assess the prescription writing practices in a government tertiary care hospital in Haryana by using WHO prescribing indicators.Methods: A total of 2155 prescriptions were evaluated. Each prescription was evaluated for average number of drugs pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…1,5 About 95.8% of drugs were prescribed from NEML/ formulary with statistically significant p-value between geriatric wards (P=0.001). Our result was supported by the studies conducted in Ethiopia (96.6%), 4 Egypt (95.4%), 15 Lao People's Republic (86.2%) 26 and Indonesia (83.07%). 11 However, lower value as compared to this study was also reported in Serbia (70%) 27 and India (66%).…”
Section: Prescribing Indicatorssupporting
confidence: 86%
“…1,5 About 95.8% of drugs were prescribed from NEML/ formulary with statistically significant p-value between geriatric wards (P=0.001). Our result was supported by the studies conducted in Ethiopia (96.6%), 4 Egypt (95.4%), 15 Lao People's Republic (86.2%) 26 and Indonesia (83.07%). 11 However, lower value as compared to this study was also reported in Serbia (70%) 27 and India (66%).…”
Section: Prescribing Indicatorssupporting
confidence: 86%
“…The reported ADT is two times higher than that reported in India (3 minutes) and much higher than that reported in KSA (1.5 minutes) and Kuwait (1 minute). 6,22,23 It is known that short ADT is insufficient to explain the dosage regimen, adverse effects of drugs and all precautions, while the reported ADT is longer in comparison to the previous studies, this might be due to the fact that the pharmacist spent a longer time explaining to the patient the insured and non-insured medication in the prescription as HICKS do not cover full insurance for all medication.…”
Section: Discussionmentioning
confidence: 74%
“…no.-9 percentage than the ideal WHO standard (100%). The percentage of dispensed drugs was found to be less than the average percent values reported at the tertiary care hospital in Ludhiana, India (100%) 36 , and Alexandria Egypt (95.5%) 37. However, an inadequate drug supply has its implications on patients' health status and patient's convenience and trust in health system.…”
Section: Discussionmentioning
confidence: 75%